Assessment of nickel oxide substituted bioactive glass-ceramic on in vitro bioactivity and mechanical properties - Vyas, Vikash Kumar; Kumar, Arepalli Sampath; Ali, Akher; and et al (Sociedad Espanola de Ceramica y Vidrio, 2016)
Many type of oxide substituted glass-ceramics like strontium, cobalt, barium and titanium have shown bioactivity with improved mechanical properties. The present work reports the in vitro bioactivity and mechanical properties of nickel oxide substituted in bioactive glass-ceramic and results were compared with 45S5 bioactive glass-ceramic. Bioactive glass ceramics were processed through controlled crystallization of their respective bioactive glasses. The formed crystalline phases in bioactive glass-ceramics were identified using X-ray diffraction (XRD) analysis. The formation of HA layer was assessed by immersing them in the simulated body fluid (SBF) for different soaking periods. The formation of hydroxyapatite was confirmed by FTIR spectrometry, SEM and pH measurement. Densities and mechanical properties of the samples were found to increase considerably with an increasing the concentration of nickel oxide. A decrease in glass transition temperature (Tg) with NiO addition showed that the nickel oxide had acted as an intermediate in smaller quantities in the bioactive glass. The cell culture studies demonstrated that the samples containing low concentration of NiO from 0 to 1.65 mol% were non-cytotoxic against osteoblast cells. Finally, this investigation clearly concluded that NiO doped bioactive glass would be potential biomaterials for biomedical applications.
Keywords: Bioactive glass ceramics; Bioactive glasses; FTIR spectrometry and cell culture; Mechanical properties; Nickel oxide